Correlation Between Morphological And Fraction Size Of Intermetallic On Fluidity Of Al-11%Si Alloy With Fe Addition - Is Prima Nanda; Bambang Suharno (Jurnal Teknik Industri, 2010)
Intermetallic morphology influence on the fluidity of alloys Al-11% Si. From the experiments, fluidity in the alloy Al-11% Si were added 0.6, 0.8, and 1.0% Fe, it was found that the higher the Fe content is added to the values decreasing fluidity. On addition of 1% Fe provides the longest phase of intermetallic 50.2 mm, while the shortest intermetallic phase is given by the addition of 0.6% Fe 21.3 mm. In the alloy Al-11% Si with the addition of Fe are generally higher and higher, would produce intermetallic area fraction increased significantly. On addition of 0.6% Fe intermetallic area fraction of 1.01%, while the addition of 0.8% and 1% Fe Fe each area fraction 1.16% and 2.26%